2022
DOI: 10.1051/0004-6361/202141375
|View full text |Cite
|
Sign up to set email alerts
|

A unified accretion-ejection paradigm for black hole X-ray binaries

Abstract: The spectral evolution of transient X-ray binaries can be reproduced by an interplay between two flows separated at a transition radius RJ: a standard accretion disk (SAD) in the outer parts beyond RJ and a jet-emitting disk (JED) in the inner parts. In the previous papers in this series we successfully recover the spectral evolution in both X-rays and radio for four outbursts of GX 339-4 by playing independently with the two parameters: RJ and the disk accretion rate Ṁin. In this paper we compare the temporal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Hereafter, we focus on such a framework, the hybrid disk configuration proposed by Ferreira et al (2006b), which has recently been successfully compared to observations in a series of papers (Marcel et al 2018a(Marcel et al ,b, 2019(Marcel et al , 2020(Marcel et al , 2022Ursini et al 2020;Marino et al 2021;Barnier et al 2022). In this framework, a large-scale vertical magnetic field B z is assumed to thread the inner disk regions, for instance, below 10 4 r g , where r g = GM/c 2 is the gravitational radius.…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, we focus on such a framework, the hybrid disk configuration proposed by Ferreira et al (2006b), which has recently been successfully compared to observations in a series of papers (Marcel et al 2018a(Marcel et al ,b, 2019(Marcel et al , 2020(Marcel et al , 2022Ursini et al 2020;Marino et al 2021;Barnier et al 2022). In this framework, a large-scale vertical magnetic field B z is assumed to thread the inner disk regions, for instance, below 10 4 r g , where r g = GM/c 2 is the gravitational radius.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this is consistent with the findings of Szanecki et al (2020), it is in contrast to their findings that the source is compact within a few gravitational radii (when modelled using the relativistically smeared reflection from the accretion disc). Variations of the inner regions and accretion flow have been explained via transitions between the jet emitting disc (JED) and standard accretion disc (SAD) framework (Marcel et al 2022) and the framework of coupled hot accretion and jet model for GBHBs and AGN (Yang et al 2015), suggesting that a two-phase accretion flow could be driving the observed variability. For 1H 0707-495, the profile of Γ is flat at lower luminosity before showing a mild positive correlation at 10 −1.7 𝐿/𝐿 Edd 10 −1.5 (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our data suggest that IGR J17091-3624 in its 2022 outburst reached a relatively high Eddington ratio because of the L-T relation in the SIMS. Depending on the accretion disk model, this can be, e.g., 30% L Edd (Abramowicz et al 2010), but depends on several parameters, such as the magnetization (e.g., Marcel et al 2022). We cannot rule out the possibility that IGR J17091-3624 reached a super-Eddington luminosity based on the available black hole mass and distance constraints.…”
Section: Did Igr J17091-3624 Reach the Eddington Limit?mentioning
confidence: 98%